Wolf Pack Activism - Brav, Alon; Dasgupta, Amil; Mathews, Richmond (Management Science, 2022)
Blockholder monitoring is central to corporate governance, but blockholders large enough to exercise significant unilateral influence are rare. Mechanisms that enable moderately sized blockholders to exert collective influence are therefore important. Existing theory suggests that engagement by moderately sized blockholders is unlikely, especially when the blocks are held by delegated asset managers who have limited skin in the game. We present a model in which multiple delegated blockholders engage target management in parallel, that is, “wolf pack activism.” Delegation reduces skin in the game, which decreases incentives for engagement. However, it also induces competition over investor capital (i.e., competition for flow). We show that this increases engagement incentives and helps ameliorate the problem of insufficient engagement, although it can also foster excess engagement. Under competition for flow, the total amount of capital seeking skilled activist managers is relevant to engagement incentives, which helps to predict when and where wolf packs arise. Flow incentives are particularly valuable in incentivizing engagement by packs with smaller members. This paper was accepted by Gustavo Manso, finance.